Reversible Photomodulation of Two-Dimensional Electron Gas in LaAlO3/SrTiO3 Heterostructures - Yang, Gyeongmo; Kim, Youngmin; Jeon, Jaeyoung; Lee, Minkyung; Kim, Doyeop; Kim, Sungkyu; Eom, Kitae; Lee, Hyungwoo (Nano Letters, 2023)
Long-lived photoinduced conductance changes in LaAlO3/SrTiO3 (LAO/STO) heterostructures enable their use in optoelectronic memory applications. However, it remains challenging to quench the persistent photoconductivity (PPC) instantly and reproducibly, which limits the reversible optoelectronic switching. Herein, we demonstrate a reversible photomodulation of two-dimensional electron gas (2DEG) in LAO/STO heterostructures with high reproducibility. By irradiating UV pulses, the 2DEG at the LAO/STO interface is gradually transformed to the PPC state. Notably, the PPC can be completely removed by water treatment when two key requirements are met: (1) the moderate oxygen deficiency in STO and (2) the minimal band edge fluctuation at the interface. Through our X-ray photoelectron spectroscopy and electrical noise analysis, we reveal that the reproducible change in the conductivity of 2DEG is directly attributed to the surface-driven electron relaxation in the STO. Our results provide a stepping-stone toward developing optically tunable memristive devices based on oxide 2DEG systems.
Keywords: LaAlO 3; LaAlO3/SrTiO3 heterostructure; Low-Frequency Noise; Memory applications; Persistent Photoconductivity; Photo modulation; Photo-induced; SrTiO 3; Two-dimensional electron gas; Two-dimensional electron gases (2DEG); LaAlO3/SrTiO3 heterostructures; low-frequency noise; oxygen vacancies; persistent photoconductivity; Photomodulation; two-dimensional electron gases